PERLINDUNGAN KONSTITUSIONAL BAGI PEKERJA INDONESIA MENURUT HUKUM KETENAGAKERJAAN PADA ERA MASYARAKAT EKONOMI ASEAN (MEA) - Anwar, Abdul Hijar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
At the end of 2015 the Asean Economic Community agreement came into effect which means that there will be a single ASEAN market and production base that has five basic elements, namely a) free flow of goods, b) free flow of services services), c) free flow of investment, d) free flow of capital, and e) free flow of skilled labor. In addition to the five basic elements, the single market and production base must also contain two important components, namely priority integration sectors (PIS) and the development of the food, agriculture and forestry sectors. In terms of the free flow of labor, not all workers can compete, the ASEAN economic community limits only to skilled workers. Through the 2015 ASEAN economic community, there will be job opportunities throughout ASEAN. Job seekers can easily enter and exit from one country to another without any obstacles from the recipient country. However, the ASEAN Economic Community Blueprint limits only to skilled labor and there is no discussion about unskilled labor. In an effort to support the transfer of skilled workers, all ASEAN member countries signed an MRA (Mutual Recognition Arrangement) on November 19, 2007 consisting of 8 MRAs, including engineering services, architectural services, nurse services ( nursing services), medical practitioners, dental practitioners, accountants services, surveying services, and tourism professionals. So it is feared that Indonesian workers do not compete with foreign workers